Cost-effectiveness of unicompartmental compared with total knee replacement: a population-based study using data from the National Joint Registry for England and Wales - Burn, E; Liddle, AD; Hamilton, TW; Judge, A; Pandit, HG; Murray, DW; Villanueva, R (BMJ Publishing Group, 2018)
Objectives To assess the value for money of unicompartmental knee replacement (UKR) compared with total knee replacement (TKR). Design A lifetime Markov model provided the framework for the analysis. Setting Data from the National Joint Registry (NJR) for England and Wales primarily informed the analysis. Participants Propensity score matched patients in the NJR who received either a UKR or TKR. Interventions UKR is a less invasive alternative to TKR, where only the compartment affected by osteoarthritis is replaced. Primary outcome measures Incremental quality-adjusted life years (QALYs) and healthcare system costs. Results The provision of UKR is expected to lead to a gain in QALYs compared with TKR for all age and gender subgroups (male: <60 years: 0.12, 60–75 years: 0.20, 75+ years: 0.19; female: <60 years: 0.10, 60–75 years: 0.28, 75+ years: 0.44) and a reduction in costs (male: <60: £−1223, 60–75 years: £−1355, 75+ years: £−2005; female: <60 years: £−601, 60–75 years: £−935, 75+ years: £−1102 per patient over the lifetime). UKR is expected to lead to a reduction in QALYs compared with TKR when performed by surgeons with low UKR utilisation but an increase among those with high utilisation (<10%, median 6%: −0.04, ≥10%, median 27%: 0.26). Regardless of surgeon usage, costs associated with UKR are expected to be lower than those of TKR (<10%: £−127, ≥10%: £−758). Conclusions UKR can be expected to generate better health outcomes and lower lifetime costs than TKR. Surgeon usage of UKR does, however, have a significant impact on the cost-effectiveness of the procedure. To achieve the best results, surgeons need to perform a sufficient proportion of knee replacements as UKR. Low usage surgeons may therefore need to broaden their indications for UKR.